Adverse cutaneous drug reactions in a single quaternary referral hospital. (29th December 2015) - Botelho, Luciane F.F.; Porro, Adriana M.; Enokihara, Milvia M.S.S.; Tomimori, Jane
Abstract: Background: Adverse cutaneous drug reactions are frequent in hospital settings and are responsible for increased morbidity, mortality, and socioeconomic costs. The objective of this study was to identify high risk factors in hospitalized patients with adverse cutaneous drug reactions. Methods: This descriptive and retrospective study was performed with data from 117 patients admitted to a quaternary hospital over 44 months. We reviewed their epidemiological data, suspected drugs, clinical presentation, histopathological diagnosis, and outcome. Statistical analysis was performed using the chi‐squared test with a significance level of 5%. Results: Anticonvulsants were responsible for 23.9% of cases followed by antibiotics (22.2%). In 29% of cases, patients were taking multiple medications that could have triggered their reactions. The most common clinical forms were exanthema (37.6%), drug reaction with eosinophilia and systemic symptoms (DRESS) (14.5%), and Stevens–Johnson syndrome/toxic epidermal necrolysis (12.8%). Anticonvulsants were associated with severe forms of adverse drug reactions. Most patients (89.7%) presented clinical improvement after treatment. There was a relationship between the use of anticonvulsants and atypical lymphocytes in the dermal infiltrate, as well as the clinical form DRESS and atypical lymphocytes in the dermal infiltrate. Conclusions: The use of anticonvulsants was a high risk factor for severe clinical forms of drug reactions. The presence of atypical lymphocyte infiltrates in the dermis could indicate the use of anticonvulsants.